Husband-Focused Education and Antenatal Care Compliance: A Quantitative Study in a Matrilineal Urang Sumando Community - Maifita, Yesi; Sansuwito, Tukimin bin; Panduragan, Santhana L. (Journal of Community Service and Society Empowerment, 2026)
Husband involvement is a key determinant of antenatal care (ANC) compliance. In Padang Pariaman Regency, this involvement is influenced by the matrilineal Urang Sumando culture, which may limit husbands’ authority in maternal health decision-making. This study aimed to analyze the association between husbands’ knowledge and attitudes and maternal ANC compliance. A cross-sectional study was conducted among 100 pregnant women–husband pairs from May to August 2025. Husbands’ knowledge and attitudes were measured using validated questionnaires, while ANC compliance was assessed through audits of the Maternal and Child Health (MCH) handbook. Data were analyzed using chi-square tests and logistic regression. The results showed that ANC compliance reached 71%. Husbands with good knowledge and positive attitudes were significantly more likely to support compliant ANC attendance, and these associations remained significant after adjusting for demographic factors. These findings indicate that culturally sensitive, husband-focused educational interventions are essential for improving ANC compliance in matrilineal communities.